EXPERIMENTAL STUDY OF BUBBLE COALESCENCE IN RHYOLITIC AND PHONOLITIC MELTS - Larsen J.F.; Denis M.-H.; Gardner J.E. (My University, 2004)
We have experimentally studied the process of bubble coalescence in rhyolite and phonolite melts of natural composition. The experiments involved decompression of water-saturated melts equilibrated at pressures and temperatures from 100 to 150 MPa and 775 to 840 °C in vertically oriented, rapid-quench capable, cold seal pressure vessels. One type of experiments (rhyolite MCR-100, 120, 150 and phonolite LSP-120 series') approximates a “static” bubble coalescence case, where we held the decompressed samples for ∼5 seconds to 4320 minutes (3 days) before quenching. The second type (rhyolite LPC-100 series) replicates an “expanding” bubble coalescence environment, where we continually decompressed the experiments at a rate of 0.5 MPa/s, examining samples quenched at ending pressures between 10 and 80 MPa. Our “static” case (MCR-100, 120, and 150, and LSP-120) results show significant increases in the modal bubble sizes and in the sizes of the largest bubbles, corresponding to measurable broadening in the size distributions. Their bubble number densities (NV) decrease as a function of hold time at their final pressures (PF), and can be fit well by power law functions. Our “expanding” case experiments (LPC-100) show a significant drop in NV during the duration of the experiments that can be fit by an exponential equation as NV vs. either time or PF. Average estimates of bulk coalescence rates indicate a ∼1 order of magnitude drop in NV for “static” case rhyolites in a 2–3 day period, and ∼2 orders of magnitude for phonolites within a 3 day period. Despite a ∼2 order of magnitude difference in viscosity, coalescene in the phonolite is only slightly faster than the rhyolite. The “expanding” case experiments show a ∼1 order of magnitude drop in NV over 180 seconds. Thus, NV's decrease 4 orders of magnitude faster in expanding vs. static bubbly rhyolite melts. Our results imply that significant bubble coalescence can occur in rhyolite magmas at relatively fast (∼20 m/s) ascent rates in the conduit. Thus, bubble interconnectivity, leading to high permeability, is possible during ascent. Bubble coalescence may occur during second boiling in magma bodies that are stalled in the crust. The timescales over which this occurs is much faster than the estimated rise rates for bubbles to reach the top of the magma chamber.